2016
DOI: 10.1111/jfbc.12274
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Astaxanthin on Primary Retinal Cells of the GerbilPsammomys ObesusCultured in DiabeticMilieu

Abstract: Astaxanthin is a major marine carotenoid with powerful antioxidant and neuroprotective properties. The in vitro protective effect of astaxanthin in adult retinal cells of the type-2 diabetic model Psammomys obesus in hyperglycemic conditions was investigated. Primary retinal cells were cultured in normal (5 mM) or high concentrations of glucose (25 and 40 mM) for 5 days and treated with 1-20 μM astaxanthin for the last 48 h of culturing. Mitochondrial dehydrogenase activity and cell viability were assessed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Furthermore, 1 μg/mL Asta caused a slight and non-significant increase in cell viability in L929 cells. L929 cell viability at 48 h after 1 and 5 μg/mL Asta treatment in the current study was similar to the findings of primary retinal cells [ 17 ], indicating that Asta dissolved in DMSO slightly reduces or increases cell viability in normal cells. Slight cell viability decreasing the effects of Asta in DMSO after 24 and 48 h exposure rationalizes the aggregation use of Asta by HAn.…”
Section: Resultssupporting
confidence: 87%
“…Furthermore, 1 μg/mL Asta caused a slight and non-significant increase in cell viability in L929 cells. L929 cell viability at 48 h after 1 and 5 μg/mL Asta treatment in the current study was similar to the findings of primary retinal cells [ 17 ], indicating that Asta dissolved in DMSO slightly reduces or increases cell viability in normal cells. Slight cell viability decreasing the effects of Asta in DMSO after 24 and 48 h exposure rationalizes the aggregation use of Asta by HAn.…”
Section: Resultssupporting
confidence: 87%
“…40 Carotenoids also have improved mitochondrial dysfunction as an important source of ROS/RNS in DR. These compounds enhanced the expression of mitochondrial dehydrogenase 51 and electron transport complex III 45 in the retinal tissue of diabetic animals. Heat shock protein 60 (HSP60) as a major mitochondrial biomarker of stress ameliorated after treatment with carotenoids.…”
Section: Discussionmentioning
confidence: 96%
“…36,39 Retinal neuronal and vascular cell apoptosis also involved in the pathogenesis of DR. Several studies showed carotenoids decreased apoptosis in retinal tissue and cell of diabetes models. 38,41,44,51 Moreover, it has been shown that these compounds mitigated the activation of caspase-3. 40,42 Recent studies have shown that retinal neuropathy plays a crucial role, especially in the early stage of DR. 65,66 Carotenoids increased the expression of retinal BDNF and prevented retinal neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes, in combination with high blood glucose may unpair the function of these cells. Likewise, a high concentration of glucose can promote photoreceptor degeneration as demonstrated in vitro by Baccouche et al [ 35 ]. ERG abnormalities found in the diurnal P .…”
Section: Discussionmentioning
confidence: 99%